SO2 Capture Using Porous Organic Cages. (10th June 2021) - Martínez‐Ahumada, Eva; He, Donglin; Berryman, Victoria; López‐Olvera, Alfredo; Hernandez, Magali; Jancik, Vojtech; Martis, Vladimir; Vera, Marco A.; Lima, Enrique; Parker, Douglas J.; Cooper, Andrew I.; Ibarra, Ilich A.; et al.
Abstract: We report the first experimental investigation of porous organic cages (POCs) for the demanding challenge of SO2 capture. Three structurally related N‐containing cage molecular materials were studied. An imine‐functionalized POC (CC3) showed modest and reversible SO2 capture, while a secondary‐amine POC (RCC3) exhibited high but irreversible SO2 capture. A tertiary amine POC (6FT‐RCC3) demonstrated very high SO2 capture (13.78 mmol g −1 ; 16.4 SO2 molecules per cage) combined with excellent reversibility for at least 50 adsorption–desorption cycles. The adsorption behavior was investigated by FTIR spectroscopy, 13 C CP‐MAS NMR experiments, and computational calculations. Abstract : Porous organic cages (POCs) were investigated for the first time for the capture of SO2 . A tertiary amine cage (6FT‐RCC3) demonstrated remarkably high SO2 capture that was perfectly reversible for at least 50 adsorption–desorption cycles.